Electrode kinetics. - Bamford, C. H.; Compton, R. G. (Comprehensive chemical kinetics ;, 1986)
Volumes 26 and 27 are both concerned with reactions occurring at electrodes arising through the passage of current. They provide a comprehensive review of the study of electrode kinetics. The basic ideas and experimental methodology are presented in Volume 26 whilst Volume 27 deals with reactions at particular types of electrodes. Chapter 1 serves as an introduction to both volumes and is a survey of the fundamental principles of electrode kinetics. Chapter 2 deals with mass transport - how material gets to and from an electrode. Chapter 3 provides a review of linear sweep and cyclic voltammetry which constitutes an extensively used experimental technique in the field. Chapter 4 discusses a.c. and pulse methods which are a rich source of electrochemical information. Finally, chapter 5 discusses the use of electrodes in which there is forced convection, the so-called ``hydrodynamic electrodes''.